1995
DOI: 10.1097/00000658-199506000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy for Cancer of the Head of the Pancreas 201 Patients

Abstract: The survival of patients with pancreatic adenocarcinoma treated by pancreaticoduodenectomy is improving. Aspects of tumor biology, such as DNA content, tumor diameter, nodal status and margin status, are the strongest predictors of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
523
6
31

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 905 publications
(581 citation statements)
references
References 31 publications
21
523
6
31
Order By: Relevance
“…Pathologic predictors of survival after surgery include vascular invasion (Griffanti-Bartoli et al, 1994), perineural invasion (Hermanek, 1998;Ozaki et al, 1999), histological tumour grade (Greer and Brennan, 1993), not achieving a clear margin (Yeo et al, 1995) and tumour size (Fortner et al, 1996). Taking all these factors into account, Fortner and co-workers (1996) reported that, in 52 patients undergoing potentially curative regional pancreatectomy, tumour size was the strongest predictor of survival independent of lymph node metastases.…”
mentioning
confidence: 99%
“…Pathologic predictors of survival after surgery include vascular invasion (Griffanti-Bartoli et al, 1994), perineural invasion (Hermanek, 1998;Ozaki et al, 1999), histological tumour grade (Greer and Brennan, 1993), not achieving a clear margin (Yeo et al, 1995) and tumour size (Fortner et al, 1996). Taking all these factors into account, Fortner and co-workers (1996) reported that, in 52 patients undergoing potentially curative regional pancreatectomy, tumour size was the strongest predictor of survival independent of lymph node metastases.…”
mentioning
confidence: 99%
“…There have also been advances in surgery, as the mortality is now less than 5% in these centers [1,2,4,5,7,8].…”
mentioning
confidence: 99%
“…In fact, pancreatic carcinoma is refractory to chemotherapy and radiotherapy. [1][2][3] Inactivation of p53, a constant feature of pancreatic carcino- Gene therapy of pancreatic cancer blocking HMGA1 F Trapasso et al ma, 27,28 could account for resistance to therapy. In fact, p53 function is required for growth arrest or apoptosis after administration of DNA-damaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for all stages of surgically resectable disease combined, the overall 5-year survival is less than 15% of cases. [1][2][3] Therefore, alternative therapeutic strategies are urgently required for pancreatic cancer. The aim of our study was to evaluate whether suppression of HMGA1 protein synthesis with an adenoviral vector could benefit patients with pancreatic cancer.…”
mentioning
confidence: 99%